Hearing dysfunction as the factor influencing the body asymmetry in 13-15 year-old youth - Wieczorek, Marta (Polish Journal of Public Health, 2009)
Introduction. Physical development is one on the human development areas and lateralization is one of its aspects. Lateralization, with its consequences as an asymmetry, is considered to be a developmental regularity and the lateralization level decides on effective operation. Hearing is very important for social life. Many more lateralization disorders could take place in hearing-impaired children. It is related to the infl uence of deafness on neurological structures and hearing-impaired people’s behaviour. Aim. The cognitive aim of the study was to identify and compare functional asymmetry in a chosen group of 13-16 year-old hearing-impaired youth. The comparison with hearing peers and identification of a problem in the context of the subjects’ gender was also carried out. Material and method. The study was carried out in hearing- impaired students of a Hearing-Impaired Education Centre placed in the south of Poland and in hearing students of public secondary school in the same localisation. The Wroclaw Asymmetry Test by Koszczyc and Sekita was used during the study. Results. The right-sided functional asymmetry dominates in examined groups of hearing and hearing-impaired girls and boys. Both groups of examined girls and group of examined hearing boys have dominant uniform profile of functional asymmetry. In case of hearing-impaired boys the combined profile prevails. The same directions and profiles of functional asymmetry are observed in hearing girls and boys. Hearing-impaired students have different functional asymmetry profiles, but the same directions. Conclusions. One can reach the conclusion, that the hearing defects determine lateralization, what is observed especially in hearing-impaired boys. Hearing defects in girls infl uence the lateralization as well, but to the smaller extent. Significant dimorphic differences in body lateralization are not observed, either.